Local content: a new instructional in EFL writing autobiography (participatory action research on tourism class) - Hamzani Wathoni; Hasan Basri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Genres-based text in the content area of writing has long been practiced, yet the theme's content sometimes does not match learners' needs-this research aimed at discovering the effectiveness of local content-based learning media in teaching English for the tourism class. The local content selected was local public figures to write an autobiography. This research applied for participatory action research taking place in one-class English for tourism. A total of fifteen course-takers for the three-month course were recruited, documenting how the idea of local content we proposed was used to teach tourism students' writing with the test as the instrument. The teaching content is restricted to two formulated indicators; comprehending text structure and language features, including using to be and pronoun. Findings indicate that local content effectively improved course takers' comprehension of the descriptive text structure and increased vocabulary. The majority of course-takers reflected a significant improvement to meet classical passing grades in the last teaching evaluation. The diagnostic test previously was under stipulated standardized-score. The course-takers successfully wrote narration using local public figures to apply" to be" in good sentences. Moreover, overlapping use of masculine and feminine was distinguished correctly and positioned in well-constructed narrative text.